2021
DOI: 10.1016/j.tig.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of cfDNA and Nuclease Biology

Abstract: Cell-free DNA (cfDNA) is a widely used noninvasive biomarker for diagnosis and prognosis of multiple disease states. Emerging evidence suggests that cfDNA might not just be passive waste products of cell death but could have a physiological and pathological function in inflammation and autoimmunity. The balance of cfDNA generation and clearance may thus be vital in health and disease. In particular, plasma nuclease activity has been linked to multiple pathologies including cancer and systemic lupus erythematos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 113 publications
1
69
0
1
Order By: Relevance
“…Increasing evidences suggested that cfDNA played an active role in inflammatory diseases. It also tightly participated in immune responses in physiological conditions and lead to sterile inflammation in pathological conditions [ 2 , 3 ]. Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences suggested that cfDNA played an active role in inflammatory diseases. It also tightly participated in immune responses in physiological conditions and lead to sterile inflammation in pathological conditions [ 2 , 3 ]. Specifically, in rheumatoid arthritis (RA) patients, the levels of cfDNA in synovial fluid (SF) and peripheral blood were highly elevated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DNase IL3 can degrade chromatin-associated DNA more efficiently than DNase I, which preferably 'eats' naked DNA [145]; DNase I is more efficient in cleaving naked DNA [144]. Apparently, DNase IL3 is not inactivated by actin in the cytoplasm or in the blood [117]. The data obtained indicate that DNase IL3 should be recruited actively during apoptotic and inflammatory processes at relatively early stages, before DNase I.…”
Section: Extracellular Secreted Dnasesmentioning
confidence: 88%
“…The half-life of cfDNA is quite short, estimated to be between 16 min and 2 h [116]. There are at least three potential mechanisms of DNA excretion from the blood: active uptake by the reticuloendothelial system in the liver and spleen, passive filtration by the renal system and direct degradation by nucleases [117].…”
Section: Dnases and Their Role In The Maintenance Of Cfdna Homeostasis Under Pathological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations